A GIS based solid waste collection modeling in Petaling Jaya, Malaysia - 429292 Lawal Billa (Skudai : Universiti Teknologi Malaysia, 2001)
Thesis (Master of Science (Urban and Regional Planning)) - Universiti Teknologi Malaysia, 2001